Accurate assessment of liver steatosis in animal models using a high throughput Raman fiber optic probe. Issue 19 (7th October 2015) - Hewitt, Kevin C.; Ghassemi Rad, Javad; McGregor, Hanna C.; Brouwers, Erin; Sapp, Heidi; Short, Michael A.; Fashir, Samia B.; Zeng, Haishan; Alwayn, Ian P.
<x xml:space="preserve">Abstract</x> A high throughput Raman fiber probe system provides accurate and rapid biochemical assessment of the hepatic fat content of livers.